Comparative Aspects of Molecular Mechanisms of Drug Resistance through ABC Transporters and Other Related Molecules in Canine Lymphoma - Hirotaka Tomiyasu; Hajime Tsujimoto (Veterinary Sciences, 2015)
The most important causes of treatment failure in canine lymphoma include intrinsic or acquired drug resistance. Thus, elucidation of molecular mechanisms of drug resistance is essential for the establishment of better treatment alternatives for lymphoma patients. The overexpression of drug transporters is one of the most intensively studied mechanisms of drug resistance in many tumors. In canine lymphoma, it has also been shown that the overexpression of drug efflux pumps such as P-glycoprotein is associated with drug-resistant phenotypes. Canine lymphoma has many pathological similarities to human non-Hodgkin’s lymphoma, and they also share similar molecular mechanisms of drug resistance. We have previously demonstrated the association of the overexpression of drug transporters with drug resistance and indicated some molecular mechanisms of the regulation of these transporters’ expressions in canine and human lymphoid tumor cells. However, it has also been indicated that other known or novel drug resistance factors should be explored to overcome drug resistance in lymphoma. In this review, we summarize the recent findings on the molecular mechanisms of drug resistance and possible strategies to develop better treatment modalities for canine lymphoma from the comparative aspects with human lymphoid tumors.